The impact of obesity on foot morphology in women aged 48 years or older - Kristína Tománková; Miroslava Přidalová; Aleš Gába (Palacký University Olomouc, 2015)
Background: Obesity is major risk factor for many diseases within society and represents extensive loads for the feet which lead to various foot disorders and deformities. Objective: The aim of this study was to evaluate the impact of obesity as represented by percent body fat (PBF) on foot morphology. Methods: The study sample included 139 Czech women aged 48-69 years. The women were divided into two groups by PBF: non-obese women (NOW) (n = 66; PBF < 35%) and obese women (OW) (n = 73; PBF > 35%). Measurements included % PBF and width, length and angle dimensions of foot. The Chippaux-Smirak index (CSI) was calculated for each foot. Results: We found significant differences between OW and NOW in these parameters: direct forefoot width (sin. p = .02, rpb = .20), direct heel width (sin. p = .01, rpb = .22; dex. p < .01, rpb = .22), hallux angle (sin. p = .01, rpb = .25) and CSI (sin. p < .01, rpb = .26; dex. p < .01, rpb = .27). The results showed that the mean values of the heel width and CSI were significantly higher in OW on both feet, the mean values of forefoot width only on the left foot. Conclusions: Results proved that obesity impacts all parts of the foot (heel, longitudinal foot arch, forefoot). Despite significant differences of the CSI between NOW and OW, the number of subjects with flat feet was in both groups negligible.